Exploiting the 2-Amino-1,3,4-thiadiazole Scaffold To Inhibit Trypanosoma brucei Pteridine Reductase in Support of Early-Stage Drug Discovery - Linciano, Pasquale; Wade, Rebecca C. (ACS omega, 2017)
Pteridine reductase-1 (PTR1) is a promising drug target for the treatment of trypanosomiasis. We investigated the potential of a previously identified class of thiadiazole inhibitors of Leishmania major PTR1 for activity against Trypanosoma brucei (Tb). We solved crystal structures of several TbPTR1-inhibitor complexes to guide the structure-based design of new thiadiazole derivatives. Subsequent synthesis and enzyme- and cell-based assays confirm new, mid-micromolar inhibitors of TbPTR1 with low toxicity. In particular, compound 4m, a biphenyl-thiadiazole-2,5-diamine with IC50 = 16 μM, was able to potentiate the antitrypanosomal activity of the dihydrofolate reductase inhibitor methotrexate (MTX) with a 4.1-fold decrease of the EC50 value. In addition, the antiparasitic activity of the combination of 4m and MTX was reversed by addition of folic acid. By adopting an efficient hit discovery platform, we demonstrate, using the 2-amino-1,3,4-thiadiazole scaffold, how a promising tool for the development of anti-T. brucei agents can be obtained.